Milo stover, forage sorghum, and protein levels compared for growing calves - K. Bolsen; J. Oltjen; H. Ilg (Kansas Agricultural Experiment Station Research Reports, 1978)
Milo stover silage, baled silo stover or forage sorghum silage was fed in 10, 12, or 14% protein rations to 120 calves in a 95-day growing trial, December 9, 1976, to March 14, 1977. Calves fed forage sorghum silage outperformed those fed milo stover silage or baled milo stover. Ensiled and baled milo stover supported similar performances. Calves fed 10% protein gained slower and less efficiently than those fed 12 or 14% protein. Observed gain and efficiency for a ration containing equal parts of milo stover silage and forage sorghum silage exceeded predicted gain and efficiency by 7.8% and 15.4%, respectively.
Keywords: Cattlemen' s Day; 1978; Report of progress (Kansas State University. Agricultural Experiment Station); 320; Beef; Milo stover; Forage sorghum; Protein; Calves